Isolation, culture and characterization of neural crest cells from lung tissue of mT/mG;Wnt1-Cre mice - DONG Xiaowen, LI Yongxin, GONG Xiaoxue, FENG Lingfang, CHEN Junfei, YAO Jiahui, LOU Jianlin (Jichu yixue yu linchuang)
Objective To isolate and culture neural crest cells (NCCs) from lung tissue of mice and to identify the characteristics of the cells in order to provide a new cell model for studying lung injury and injure repair. Methods The mT/mG dual-fluorescence reporter mice and Wnt1-Cre transgenic mice were hybridized, and mT/mG; Wnt1-Cre transgenic mice were screened to obtain enhanced green fluorescent protein (EGFP) permanently labeled NCCs. Cell suspension of mouse lung tissue was prepared by enzymolysis. EGFP+ cells (namely NCCs) were harvested by flow cytometry. Primary culture was performed with DMEM/F12 culture medium optimized in the laboratory, NCCs was characterized by immunofluorescence microscopy. Then NCCs differentiation was directed by mouse bone marrow mesenchymal stem cells osteogenic induction. Results The mT/mG of EGFP permanently labeled NCCs was successfully obtained by hybridization and high-purity NCCs were isolated from Wnt1-Cre transgenic mice lung tissue. They can be cultured in vitro and with spindle morphology which was,similar to fibroblast adherent proliferation. NCCs expressed the neural crest stem cell marker Sox10 and induced to differentiate into osteoblasts. Conclusions NCCs isolated and cultured from lung tissue of mT/mG;Wnt1-Cre transgenic mice show stable proliferation and have the characteristics of neural crest stem cells, which may function as a potential cell model for research on lung tissue injury and the mechanism of repair.